Identifying Students’ Learning Styles in English Language Education - Veamas Wahyu Saputra; Hardianti Hardianti (Publikasi Indonesia, 2026)
In the context of rapid educational development, understanding students’ learning styles has become increasingly important for improving the effectiveness of English language teaching, particularly in English as a Foreign Language (EFL) setting where exposure to the language is limited. This research investigates the learning style preferences of EFL students in the English Education Program at Universitas Esa Unggul. The study was motivated by the fact that many students are not fully aware of their own learning styles, which may influence the effectiveness of their English language learning. Using a descriptive qualitative method, data were collected from 10 participants through questionnaires and interviews based on the VARK framework (Visual, Auditory, Read/Write, and Kinesthetic). The findings revealed that students demonstrated varied preferences across the four categories, with some showing a dominant single style and others displaying multimodal tendencies by combining two or more styles. These results indicate that identifying students’ learning styles can provide valuable insights for improving teaching strategies in EFL classrooms. The study contributes to learner-centered English language education by encouraging teachers to integrate diverse instructional methods that address different learning preferences.